EWaS3 2018 2018
DOI: 10.3390/proceedings2110620
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Drainage Density Parameter Estimation within Erosion Potential Method

Abstract: This paper analyses the possibilities to derive drainage density map, a parameter used within Erosion Potential Method (EPM, Gavrilović), for the Dubračina catchment study area in better detail and precision. EPM method is used for erosion assessment in the karstic areas characterized by torrential rivers. In this paper, three different methodologies were used to derive drainage density map each using different assumptions and allowing different spatial variability. The third case of drainage density map provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In addition to the scale effect of their area, it has been demonstrated that parameters such as slope, land cover, lithology, and soil erosivity have an effect on sediment budget (Van Oost et al 2000;Yan et al 2013;de Vente et al 2013;Fang et al 2016;Messina and Biggs 2016). Moreover, the link between higher drainage density and higher sediment yield is only present in homogeneous bedrock geology (Dragičević et al 2018). In addition, the connectivity of the river networks also plays a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the scale effect of their area, it has been demonstrated that parameters such as slope, land cover, lithology, and soil erosivity have an effect on sediment budget (Van Oost et al 2000;Yan et al 2013;de Vente et al 2013;Fang et al 2016;Messina and Biggs 2016). Moreover, the link between higher drainage density and higher sediment yield is only present in homogeneous bedrock geology (Dragičević et al 2018). In addition, the connectivity of the river networks also plays a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of figure (9) it is concluded that the temperature degrees vary between 0.31℃ and 1.97℃. The entire eastern part of the basin has coefficients greater than 1 which is explained by the dominance of high altitudes and the low density of vegetation cover, and in return The only places with a low coefficient are located at the level of the valleys and their thalwegs.…”
Section: Temperature Coefficient (T)mentioning
confidence: 90%
“…The linear parameters are analyzed for the stream order, stream length, mean stream length, and bifurcation ratio (Harsha et al, 2020). The mean stream length is related to the drainage network and corresponds with its surface (Dragičević et al, 2018;Pondari et al, 2020). The shape parameters include the form factor, shape factor, elongation ratio, compactness coefficient, and circulatory ratio (Al-Assadi, 2020; Saha et al, 2020).…”
Section: Referencesmentioning
confidence: 99%